Botanic Gardens, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
This postcard offers a scenic view of the Botanical Gardens located in Port of Spain, Trinidad.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago